2017
DOI: 10.1016/j.jfda.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage temperature and time on the nutritional quality of walnut male inflorescences

Abstract: The objective of this study was to investigate the effect of storage temperature and time on nutrients, bioactive compounds, and antioxidant activities of walnut male inflorescences. The results showed that the moisture, saccharides, fat, protein, amino acids, ascorbic acid, phenolic and flavonoid compound contents, and antioxidant activities of walnut male inflorescences were markedly influenced by storage temperature, and different degrees of decrease in these parameters were observed during the entire stora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
5
12
0
1
Order By: Relevance
“…It could be said that temperature and storage period effect to nutrient degradation and these were the beginning of a shoot deterioration. This result was in agreement with Zhang et al (2017), reported that storage temperature and time were important factors which effected on nutrients and the storage in low temperature could maintain a high level of nutritive constituents compared with storage in room temperature. Moreover, Ding et al (1997), Ding et al (2006) and Song et al (2013) reported that temperature plays as a major role in causing senescence of agriculture product.…”
Section: Total Acidity Sugar Content and Proximate Analysissupporting
confidence: 92%
“…It could be said that temperature and storage period effect to nutrient degradation and these were the beginning of a shoot deterioration. This result was in agreement with Zhang et al (2017), reported that storage temperature and time were important factors which effected on nutrients and the storage in low temperature could maintain a high level of nutritive constituents compared with storage in room temperature. Moreover, Ding et al (1997), Ding et al (2006) and Song et al (2013) reported that temperature plays as a major role in causing senescence of agriculture product.…”
Section: Total Acidity Sugar Content and Proximate Analysissupporting
confidence: 92%
“…An Al‐foil‐laminated bag can protect the product from oxygen, water vapor, and ultraviolet light, which are factors that affect the stability of biological activity (Prasad & Kochhar, ). Low temperature storage can be effective in maintaining the contents of bioactive compounds (Zhang, Wang, Shi, & Pan, ). Based on the results, we suggest that hydrolyzate be stored in an Al‐foil‐laminated bag at 4°C to maintain its biological activity, ensure a low moisture content and provide for long‐term storage.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrolysis is a damaging process of fat caused by high water content (Frankel, 2012). The high ash content of the product because ash as an inorganic matter is unsusceptible to the environmental condition and physiological activity (Zhang et al, 2017). Meanwhile, the TDN content did not differ because although the crude protein and crude fiber received by farmers show lower value, the crude fat content is high.…”
Section: Nutrient Content Of Concentratementioning
confidence: 99%